Maria e o "charisma" de Deus: esboços de uma mariologia carismática e a possibilidade de diálogo entre pentecostais e católicos - Vasconcelos, Henrique Mata de (Gregorianum, 2024)
Mary seems to have been forgotten in the Protestant tradition, especially in the Pentecostal branch. There is excessive enthusiasm regarding her in Charismatic Catholic circles. In common, we find a need for a charismatic theology around Mary, i.e., a Charismatic Mariology. This article aims to meet this need. To that end, I will first outline how Mary and the Mariological question is present in Pentecostalism. Second, I will investigate how Mary appears in the New Testament, according to a charismatic point of view. Third, I will explore the possibilities of ecumenical dialogue around this Charismatic/Pneumatic Mariology. I will conclude that Mary appears in the New Testament as a woman filled with the Spirit, as a charismatic and a charisma of God. Moreover, this way of looking at her, as a woman who carries and who channels the Spirit and the divine charis, can make a particular contribution to the Catholic charismatic movement. Furthermore, this charismatic Mariology is a prospective way to foster a pneumatic and dialectical dialogue between Protestants and Catholics, especially, but not only, of the charismatic branches.